THE IMPACT OF HUMAN CAPITAL DEVELOPMENT ON AGRICULTURAL OUTPUT IN NIGERIA - NNANA OKOI OFEM; TANGBAN EGBE EBAGU; WILLIE WILFRED OKOI; RITA NGOZI OKAFOR (International Studies Journal)
This study employed the Ordinary Least Square (OLS) estimation technique to examine the impact of human capital development on agricultural productivity in Nigeria for the period 1981-2022. The objectives of the study were to examine the impact of aggregate investment in education on agricultural output, and aggregate investment in healthcare on agricultural output in Nigeria. The findings showed that aggregate expenditure on education has a positive and significant effect on agricultural output in Nigeria, as well as labour force participation, and life expectancy at birth having a positive and statistically significant effect on agricultural output in Nigeria. On the contrary, aggregate expenditure on healthcare and literacy rate both showed a negative and not statistically significant on agricultural output in Nigeria. This study is inclined to the fact that a high literacy rate and well- being of the citizens contribute greatly to gross domestic product in Nigeria. The study further recommended that; Nigeria government should increase funding in the education sector to sustain the positive outcome of the current spending this will improve literacy rate which is essential for economic growth and development.